Nitrogen oxide in protostellar envelopes and shocks: the ASAI survey. Issue 4 (11th December 2017) - Codella, C; Viti, S; Lefloch, B; Holdship, J; Bachiller, R; Bianchi, E; Ceccarelli, C; Favre, C; Jiménez-Serra, I; Podio, L; Tafalla, M
Abstract: The high sensitivity of the IRAM 30-m Astrochemical Surveys At IRAM (ASAI) unbiased spectral survey in the mm window allows us to detect NO emission towards both the Class I object SVS13-A and the protostellar outflow shock L1157-B1. We detect the hyperfine components of the 2 Π1/2 J = 3/2 → 1/2 (at 151 GHz) and the 2 Π1/2 J = 5/2 → 3/2 (at 250 GHz) spectral pattern. The two objects show different NO profiles: (i) SVS13-A emits through narrow (1.5 km s −1 ) lines at the systemic velocity, while (ii) L1157-B1 shows broad (∼5 km s −1 ) blueshifted emission. For SVS13-A, the analysis leads to T ex ≥ 4 K, N (NO) ≤ 3 × 10 15  cm −2, and indicates the association of NO with the protostellar envelope. In L1157-B1, NO is tracing the extended outflow cavity: T ex ≃ 4–5 K, and N (NO) = 5.5 ± 1.5 × 10 15  cm −2 . Using C 18 O, 13 C 18 O, C 17 O, and 13 C 17 O ASAI observations, we derive an NO fractional abundance less than ∼10 −7 for the SVS13-A envelope, in agreement with previous measurements towards extended photodissociation regions (PDRs) and prestellar objects. Conversely, a definite X (NO) enhancement is measured towards L1157-B1, ∼6 × 10 −6, showing that the NO production increases in shocks. The public code uclchem was used to interpret the NO observations, confirming that the abundance observed in SVS13-A can be attained in an envelope with a gas density of 10 5  cm −3 and a kinetic temperature of 40 K. The NO abundance in L1157-B1 is reproduced with pre-shock densities of 10 5  cm −3 subjected to a ∼45 km s −1 shock.